Synthesis of Rare-Earth Nanomaterials Ag-Doped NaYF4:Yb3+/Er3+@NaYF4:Nd3+@NaGdF4 for In Vivo Imaging - Wei Zhang; Yang Zang; Yanli Lu; Jinghui Han; Qingyun Xiong; Jinping Xiong (Nanomaterials, 2022)
In this study. a novel near-infrared fluorescent-driven contrast agent (Ag-doped NaYF4:Yb3+/Er3+@NaYF4:Nd3+@NaGdF4) was synthesized using a coprecipitation-hydrothermal-solvothermal-solvothermal (CHSS) method. The results shows that hexagonal NaYF4:Yb3+/Er3+ with a diameter of 300 nm was successfully synthesized by the CHSS method. The new contrast agent was characterized using scanning electron microscopy, fluorescence spectrometry, transmission electron microscopy, energy-dispersive spectrometry and ultraviolet-visible light diffuse reflectance absorption spectroscopy. Even at low concentrations (0.2 M), this proposed contrast agent can be excited by near-infrared light with a wavelength of 980 nm and emits a dazzling green light with a wavelength of 540 nm, and the comparison of the luminescence intensity proves that doping with silver increases the luminescence intensity of the upconverted nanomaterial by nearly 13 times based on the calculated quantum yield. TEM images show the successful preparation of silver nanoparticles with a diameter of 30 nm, and the energy spectrum shows the successful doping of silver nanoparticles and the successful preparation of the core-shell structure of NaYF4:Yb3+/Er3+@NaYF4:Nd3+@NaGdF4. Furthermore, the mechanism of the increased luminous intensity has been studied using simulation calculations. Finally, cytotoxicity tests were used to test material which was modified by 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[amino(polyethylene glycol)-2000] (DSPE-PEG2K), and the biocompatibility was significantly improved, meeting the standard for biological applications.